Design and real-time implementation of an internal model speed control for an induction motor - Mohamed, H.A.F.; Yang, S.S.; Moghavvemi, M. (2008)
This paper carries out the design and real time implementation of an Internal Model Controller (IMC) to control the speed of an induction motor and precisely a squirrel cage type. The scheme in this paper is constructed using a model and a controller both being Artificial Neural Network (ANN) based. This ANN-based control scheme has been chosen because of its ability to handle the strong nonlinearities of the induction motor. The performance of the controller is tested by applying different types of input signals as well as load torque disturbances. Whether loaded or unloaded, the proposed internal model controller has proved to achieve high performance and accuracy.